2002
DOI: 10.2166/wst.2002.0422
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid two-phase system for anaerobic digestion of food waste

Abstract: A hybrid two-phase system, consisting of a solid waste reactor as the acidification reactor and a wastewater reactor, i.e. an upflow anaerobic sludge blanket (UASB) reactor, as the methanogenic reactor, for anaerobic digestion of food waste was investigated. After the pre-acidification stage, COD and total VFA removals in the methanogenic phase were in the ranges of 74-93% and 77-100%, respectively, while leachate COD and total VFA concentrations in the acidification phase decreased by 95% and 97-99%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…3(b)). As expected, a higher concentration of acetic acid than propionic acid was found (between 15-and 20-fold), which mostly occurs in the presence of high protein and lipid containing substrates or in high-strength substrates like solid waste [17]. The values of the alkalinity ratios were maintained around 0.42 and 0.3 for ASBR1 and ASBR2, respectively, indicating a stable process, especially for ASBR2.…”
Section: Start-upsupporting
confidence: 69%
“…3(b)). As expected, a higher concentration of acetic acid than propionic acid was found (between 15-and 20-fold), which mostly occurs in the presence of high protein and lipid containing substrates or in high-strength substrates like solid waste [17]. The values of the alkalinity ratios were maintained around 0.42 and 0.3 for ASBR1 and ASBR2, respectively, indicating a stable process, especially for ASBR2.…”
Section: Start-upsupporting
confidence: 69%
“…The gradual increase in VS removal rate was associated with the growth of methanogenic microorganisms over the period of time that facilitated better VS removal efficiency. Relatively low VS removal (57-60%) in the HASL system was reported by Wang et al (2002). Fig.…”
Section: Overall Removal Efficienciesmentioning
confidence: 82%
“…The goal is to improve the performance of the reactor by allowing enough buffering capacity and space for respective microbial communities to flourish under suitable conditions. Adding on to this, a two-phase hybrid anaerobic solid-liquid system (HASL) by Wang et al (2002Wang et al ( , 2003 and Liu et al (2008), was studied in detail for FW digestion and has shown promising results. Apart from these reactor types, an up-flow anaerobic sludge blanket process elaborately reviewed by Chong et al (2012) is extensively applied for wastewater treatment with relatively high removal efficiency at short hydraulic retention times (HRTs), but is also considered not suitable for wastes with high solid content such as municipal FW (Tawfik et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…This is clear from the fact that they have been successively used for digestion of food wastes containing high solids concentrations (Hai-Lou et al 2002;Wang et al 2002Wang et al , 2003 as well as that of swine (Lo et al 1994) and dairy (Co´rdoba et al 1995) operations. Even though it represents a viable option, hybrid process configurations for anaerobic digestion of manure have been the subject of a very limited number of investigations on poultry and swine manure (Yang et al 1989(Yang et al , 1993 and none on dairy manure.…”
Section: Introductionmentioning
confidence: 99%